HUBUNGAN PENGETAHUAN DAN PERILAKU BIDAN PRAKTEK MANDIRI TERHADAP PELAKSANAAN KELAS IBU HAMIL DI WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM TAHUN 2017 - Dewi, Rima; Yunita, Prasida (Universitas Batam, 2017)
One of the Indonesian government programs organized by the Ministry of Health is the pregnancy class for prenatal mothers attempted to enhance their knowledge as well as to change the attitude toward the childbirth process. The most common activity in a pregnancy class is discussing their guide book on delivery process. The purpose of this study to determine the correlation of the independent midwives’ knowledge levels and attitude on their pregnancy classes performance, mainly the ones at the service area of Batu Aji Health Center. As the research design, the researchers used cross-sectional approach to investigate 41 independent midwives as the respondents. The data was analyzed by Chi-Square statistical test. The result presents that 39% midwives have lack of knowledge on conducting the pregnancy class and 41.5% of them show less appropriate attitude on guiding the pregnancy class, besides, it is also found that 20% the performance of the pregnancy class they handled is still low. The Chi-Square test obtains the correlations by p-value = 0.017 for knowledge of the midwives and the class performance and p-value = 0.000 for the attitude of midwives and the class performance. Therefore, based on the findings, it can be concluded that the pregnancy classes handled by the independent midwives are considered to have low quality standard. For this reason, it is suggested that the independent midwives have to boost and advance their knowledge as well as attitude in coaching the pregnancy class in the future to be better.